The Marxists and the Jewish Question: The History of a Debate (1843-1943) - Mitchell, Harvey (Labour / Le Travail, 1996)
The article reviews the book "The Marxists and the Jewish Question: The History of a Debate (1843-1943)," by Enzo Traverso.
Keywords: BOOKS – Reviews; Communists; MARXISTS & the Jewish Question: The History of a Debate 1843-1943; The (Book); Nonfiction; TRAVERSO; Enzo